2002
DOI: 10.1161/01.atv.0000013284.47317.95
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatic Lipase, Lipoprotein Lipase, and Cholesteryl Ester Transfer Protein to LDL and HDL Heterogeneity in Healthy Women

Abstract: Abstract-Hepatic lipase (HL) and cholesteryl ester transfer protein (CETP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 55 publications
6
44
0
6
Order By: Relevance
“…In Mexican-American population from San Antonio Family Heart Study, the authors [31] found no evidence for major locus effect on HDL-C levels after adjustment for apo A1 levels. While Carr et al [32] found association of buoyant LDL among carriers of -514T allele in pre-menopausal women, in Framingham Offspring Study with 2,667 subjects no association was seen [15]. These discrepancies could have been due to differences in the methods used for estimating sdLDL.…”
Section: Discussionmentioning
confidence: 93%
“…In Mexican-American population from San Antonio Family Heart Study, the authors [31] found no evidence for major locus effect on HDL-C levels after adjustment for apo A1 levels. While Carr et al [32] found association of buoyant LDL among carriers of -514T allele in pre-menopausal women, in Framingham Offspring Study with 2,667 subjects no association was seen [15]. These discrepancies could have been due to differences in the methods used for estimating sdLDL.…”
Section: Discussionmentioning
confidence: 93%
“…It has been demonstrated that cholesteryl ester transfer protein (CETP) is also an important determinant of LDL particle size 25,26) . In addition, lipoprotein lipase (LPL) activity and hepatic lipase activity have been shown to contribute to the formation of sd-LDL particles and could well represent significant determinants of LDL-peak particle diameter (LDL-PPD) in FH 27) . In the previous report, LDL-PPD in FH was significantly smaller than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a major quantitative trait locus on chromosome 17q21 affecting LDL-PPD has been identified (34). In addition, certain constituents of lipoprotein metabolism, such as lipoprotein lipase activity and hepatic lipase activity, have been shown to contribute to the formation of small, dense LDL particles and could well represent significant determinants of LDL-PPD in FH (22).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma CETP mass concentration was used to assess plasma CETP activity because they are strongly correlated (22). However, sample handling and storage conditions may influence the stability of lipid transfer activity and, consequently, could have a significant impact on the relationship between CETP mass and activity.…”
Section: Measurement Of Cetp Massmentioning
confidence: 99%